Prevalencia de giardia lamblia en caninos “canis lupus familiaris” asintomáticos del albergue municipal en la ciudad de Santo Domingo de los Tsáchilas. - Paredes Santamaría, Carlos Alberto (2020)
This research was carried out with the objective of determining the prevalence of the microorganism Giardia lamblia, in asymptomatic canines of the Municipal Shelter of the city of Santo Domingo de los Tsáchilas. The main problem revolves around a potential risk of zoonosis, so its control is vital especially in sites of high concentration of animals, where contagion to humans can occur. The methodology used for research is quantitative and descriptive. For the execution of the investigation, two techniques were proposed: application of coproparasitic exams and use of Uranotest diagnostic kits to determine Giardia lamblia. Samples of faecal material were collected from 37 asymptomatic canines that were in the shelter. The samples were deposited in conventional sterile plastic boxes that were used to transport them to the Universalab laboratory, where the coproparasitic examinations were performed, while the samples for the Uranotest kit were applied in the same shelter, in collaboration with the work team with which the place counts. A prevalence of Giardia of 29.73% was determined with the two techniques selected, this being a high level compared to other local and international works, which indicates a high possibility of contagion to the rest of the animals in the shelter, being able to lead to a zoonosis in the staff and those interested in adopting a canine.